Automatic Generation Algorithm of Distribution Network Topology Based on Hierarchical Layout - Guiyun YANG; Qian WU; Yankun CAO; Xiaoyu HOU; Hua SUN; Jian WANG (发电技术)
The automatic generation algorithm of topology is the core of automatic generation of distribution network topology wiring diagram. Therefore, the basic idea of automatic generation algorithm of distribution network topology was described in detail. The core of the algorithm is to search the maximum distance between two points by using the depth first search (DFS) algorithm. At the same time, the idea of hierarchical layout and comprehensive implementation was put forward. The specific implementation was divided into three layers: firstly, determining the topology layout array of a single feeder; secondly, determining the topology layout array between two substations; finally, determining the topology layout array among all substations. The layout array between two substations was filled into the layout array of all substations to get the layout array of the whole distribution network. According to the coordinate position and interconnection information of each substation and equipment determined by the layout array of the whole network, the topology wiring diagram of the whole network was generated. This method solves the problem that the solution process is very complicated or even no solution caused by directly obtaining the coordinates of all distribution network equipment in the topology wiring diagram at one time, effectively avoids the cross and greatly reduces the mapping time. Finally, the effectiveness and applicability of the algorithm were verified by practical engineering application.